Molecular Insights into the dynamics of pharmacogenetically important N-terminal variants of the human beta(2)-adrenergic receptor - Shahane, Ganesh; Parsania, Chirag; Sengupta, Durba; Joshi, Manali (Plos Computational Biology, 2014)
The human beta(2)-adrenergic receptor (beta(2)AR), a member of the G-protein coupled receptor (GPCR) family, is expressed in bronchial smooth muscle cells. Upon activation by agonists, beta(2)AR causes bronchodilation and relief in asthma patients. The N-terminal polymorphism of beta(2)AR at the 16th position, Arg16Gly, has warranted a lot of attention since it is linked to variations in response to albuterol (agonist) treatment. Although the beta(2)AR is one of the well-studied GPCRs, the N-terminus which harbors this mutation, is absent in all available experimental structures. The goal of this work was to study the molecular level differences between the N-terminal variants using structural modeling and atomistic molecular dynamics simulations. Our simulations reveal that the N-terminal region of the Arg variant shows greater dynamics than the Gly variant, leading to differential placement. Further, the position and dynamics of the N-terminal region, further, affects the ligand binding-site accessibility. Interestingly, long-range effects are also seen at the ligand binding site, which is marginally larger in the Gly as compared to the Arg variant resulting in the preferential docking of albuterol to the Gly variant. This study thus reveals key differences between the variants providing a molecular framework towards understanding the variable drug response in asthma patients.

Structural insights and functional implications of inter-individual variability in beta(2)-adrenergic receptor - Tandale, Aditi; Joshi, Manali; Sengupta, Durba (Scientific Reports, 2016)
The human beta(2)-adrenergic receptor (beta(2)AR) belongs to the G protein-coupled receptor (GPCR) family and due to its central role in bronchodilation, is an important drug target. The inter-individual variability in beta(2)AR has been implicated in disease susceptibility and differential drug response. In this work, we identified nine potentially deleterious non-synonymous single nucleotide polymorphisms (nsSNPs) using a consensus approach. The deleterious nsSNPs were found to cluster near the ligand binding site and towards the G-protein binding site. To assess their molecular level effects, we built structural models of these receptors and performed atomistic molecular dynamics simulations. Most notably, in the Phe290Ser variant we observed the rotameric flip of Trp286(6.48), a putative activation switch that has not been reported in beta(2)AR thus far. In contrast, the variant Met82Lys was found to be the most detrimental to epinephrine binding. Additionally, a few of the nsSNPs were seen to cause perturbations to the lipid bilayer, while a few lead to differences at the G-protein coupling site. We are thus able to classify the variants as ranging from activating to damaging, prioritising them for experimental studies.

What can simulations tell us about GPCRs: integrating the scales - Sengupta, Durba; Joshi, Manali; Athale, Chaitanya A.; Chattopadhyay, Amitabha (G Protein-Coupled Receptors: Signaling, Trafficking and Regulation, 2016)
The functional dynamics of G protein-coupled receptors (GPCRs) encompasses multiple spatiotemporal scales, ranging from femtoseconds to seconds and Angstroms to micrometers. Computational approaches, often in close collaboration with experimental methods, have been invaluable in unraveling GPCR structure and dynamics at these various hierarchical levels. The binding of natural and synthetic ligands to the wild-type and naturally occurring variant receptors have been analyzed by several computational methods. The activation of receptors from the inactive to the active state has been investigated by atomistic simulations and ongoing work on several receptors will help uncover general and receptor-specific mechanisms. The interaction of GPCRs with complex membranes that contain phospholipids and cholesterol have been probed by coarse-grain methods and shown to directly influence receptor association. In this chapter, we discuss computational approaches that have been successful in analyzing each scale of GPCR dynamics. An overview of these approaches will allow a more judicious choice of the appropriate method. We hope that an appreciation of the power of current computational approaches will encourage more critical collaborations. A comprehensive integration of the different approaches over the entire spatiotemporal scales promises to unravel new facets of GPCR function.

Characterizing clinically relevant natural variants of GPCRs using computational approaches - Sengupta, Durba; Sonar, Krushna; Joshi, Manali (Methods in cell biology, 2017)
G protein-coupled receptors (GPCRs) are an important class of drug targets owing to their physiological role. A large number of clinically relevant single nucleotide polymorphisms (SNPs) have been observed in GPCRs that are linked to disease susceptibility and adverse drug response. It is therefore important to characterize the variants in order to improve GPCR therapeutics. Here, we discuss computational methods coupling molecular dynamics simulations with docking and free energy calculations to characterize the functional differences in GPCR variants. The hallmark of this approach is the explicit incorporation of receptor and membrane dynamics that allows us to analyze short- and long-range effects in the variant receptors. We use the SNPs reported in β2-adrenergic receptor (β2AR) as a test case and highlight the recent successes in analyzing structural and dynamic differences in a series of population variants. The computational approach we discuss here has a twofold benefit: it helps to unravel the molecular mechanisms underlying hypo- or hyperfunctionality of variant receptors as well as prioritizing novel variants that must be experimentally tested.

Membrane-induced organization and dynamics of the N-terminal domain of chemokine receptor CXCR1: insights from atomistic simulations - Kharche, Shalmali; Joshi, Manali; Sengupta, Durba; Chattopadhyay, Amitabha (Chemistry and Physics of Lipids, 2018)
The CXC chemokine receptor 1 (CXCR1) is an important member of the G protein-coupled receptor (GPCR) family in which the extracellular N-terminal domain has been implicated in ligand binding and selectivity. The structure of this domain has not yet been elucidated due to its inherent dynamics, but experimental evidence points toward membrane-dependent organization and dynamics. To gain molecular insight into the interaction of the N-terminal domain with the membrane bilayer, we performed a series of microsecond time scale atomistic simulations of the N-terminal domain of CXCR1 in the presence and absence of POPC bilayers. Our results show that the peptide displays a high propensity to adopt a beta-sheet conformation in the presence of the membrane bilayer. The interaction of the peptide with the membrane bilayer was found to be transient in our simulations. Interestingly, a scrambled peptide, containing the same residues in a randomly varying sequence, did not exhibit membrane-modulated structural dynamics. These results suggest that sequence-dependent electrostatics, modulated by the membrane, could play an important role in folding of the N-terminal domain. We believe that our results reinforce the emerging paradigm that cellular membranes could be important modulators of function of G protein-coupled receptors such as CXCR1.
Keywords: All atom MD simulations; beta-sheet; CXCR1; Membrane interaction; N-terminal

Differential dynamics underlying the Gln27Glu population variant of the beta(2)-adrenergic receptor - Bhosale, Sumedha; Nikte, V. Siddhanta; Sengupta, Durba; Joshi, Manali (Journal of Membrane Biology, 2019)
The beta (2)-adrenergic receptor (beta (2)AR) is a membrane-bound G-protein-coupled receptor and an important drug target for asthma. Clinical studies report that the population variant Gln27Glu is associated with a differential response to common asthma drugs, such as albuterol, isoproterenol and terbutaline. Interestingly, the 27th amino acid is positioned on the N-terminal region that is the most flexible and consequently the least studied part of the receptor. In this study, we probe the molecular origin of the differential drug binding by performing structural modeling and simulations of the wild-type (Gln) and variant (Glu) receptors followed by ensemble docking with the ligands, albuterol, isoproterenol and terbutaline. In line with clinical studies, the ligands were observed to interact preferentially with the Glu variant. Our results indicate that the Glu residue at the 27th position perturbs the network of electrostatic interactions that connects the N-terminal region to the binding site in the wild-type receptor. As a result, the Glu variant is observed to bind better to the three ligands tested in this study. Our study provides a structural basis to explain the variable drug response associated with the 27th position polymorphism in the beta (2)AR and is a starting step to identify genotype-specific therapeutics.
Keywords: beta(2)-Adrenergic receptor; G-protein-coupled receptor; GPCR; molecular dynamics; Pharmacogenetics; SNP

In vitro and in silico studies on membrane interactions of diverse Capsicum annuum flower gamma-thionin peptides - Nikte, Siddhanta; Gahankari, Apurva; Mulla, Javed; Sengupta, Durba; Joshi, Manali; Tamhane, Vaijayanti (Proteins-Structure Function and Bioinformatics, 2019)
Thionins are small, cysteine-rich peptides that play an important role in plant defense, primarily through their interactions with membranes. Eight novel gamma-thionin peptides (CanThio1-8) were isolated from the flower of Capsicum annuum. Sequence analysis revealed that the peptides cluster into three groups. A representative peptide from each group (CanThio1, 2, and 3) was used for experimental characterization. Interestingly, peptides were found to possess some cytotoxic activity against normal human embryonic kidney cell line but higher cytotoxicity against cancer cell line MCF-7. CanThio3 peptide was chosen as a representative peptide to study the molecular mechanism of action on membranes. Microsecond timescale atomistic simulations of CanThio3 were performed in the presence of a POPC (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine) lipid bilayer. Simulations revealed that CanThio3 interacts with the bilayer and causes lipid thinning in the vicinity. Nonpolar amino acids specific to the alpha-core region of CanThio3 along with nonpolar residues in the gamma-core region are seen to interact with the lipid tails. The differences in the amino acid sequence of CanThio peptides in these regions explain the variability in cytotoxic activities. In summary, our results demonstrate the membrane-mediated activity of a novel series of gamma-thionin peptides from C. annuum.
Keywords: Capsicum annuum; Cytotoxicity; gamma-thionin; MD simulations; Membrane

Conformational plasticity and dynamic interactions of the N-terminal domain of the chemokine receptor CXCR1 - Kharche, Shalmali; Joshi, Manali; Chattopadhyay, Amitabha; Sengupta, Durba (Plos Computational Biology, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The dynamic interactions between G protein-coupled receptors (GPCRs) and their cognate protein partners are central to several cell signaling pathways. For example, the association of CXC chemokine receptor 1 (CXCR1) with its cognate chemokine, interleukin-8 (IL8 or CXCL8) initiates pathways leading to neutrophil-mediated immune responses. The N-terminal domain of chemokine receptors confers ligand selectivity, but unfortunately the conformational dynamics of this intrinsically disordered region remains unresolved. In this work, we have explored the interaction of CXCR1 with IL8 by microsecond time scale coarse-grain simulations, complemented by atomistic models and NMR chemical shift predictions. We show that the conformational plasticity of the apo-receptor N-terminal domain is restricted upon ligand binding, driving it to an open C-shaped conformation. Importantly, we corroborated the dynamic complex sampled in our simulations against chemical shift perturbations reported by previous NMR studies and show that the trends are similar. Our results indicate that chemical shift perturbation is often not a reporter of residue contacts in such dynamic associations. We believe our results represent a step forward in devising a strategy to understand intrinsically disordered regions in GPCRs and how they acquire functionally important conformational ensembles in dynamic protein-protein interfaces.

Identification of a novel series of potent organosilicon mosquito repellents - Kulkarni, Akshay S.; Ramesh, Remya; Walia, Safal; Sayyad, Shahebaz I.; Gathalkar, Ganesh B.; Balamkundu, Seetharamsing; Joshi, Manali; Sen, Avalokiteswar; Reddy, D. Srinivasa (ACS Omega, 2021)
Mosquito control by personal protection is one of the most efficient ways of curtailing deadly diseases such as malaria and dengue with the potential to save millions of lives per year. DEET (N,N-diethyl-3-methyl benzamide) is currently considered as the gold standard for mosquito repellents, being used for the past several decades. Control by DEET, however, is being threatened by emerging resistance among mosquitoes. To address this concern and also to improve protection times, we synthesized a novel series of 25 silicon-containing acyl piperidines using acid–amine coupling protocol and tested their activity against Aedes aegypti in mosquito-repellent assays. Several compounds from this series appear to possess good mosquito-repellent properties. Most notably, at 0.5 mg/cm2 concentrations, the mean protection time for NDS100100 was 756 min, which was higher than that of DEET (616 min). The details of design, synthesis, and biological evaluation are discussed herein.

Loss of a water-mediated network results in reduced agonist affinity in a beta(2)-adrenergic receptor clinical variant - Nikte, V. Siddhanta; Sonar, Krushna; Tandale, Aditi; Joshi, Manali; Sengupta, Durba (Biochimica ET Biophysica Acta-Proteins and Proteomics, 2021)
The beta(2)-adrenergic receptor (beta(2)AR) is a member of the G protein-coupled receptor (GPCR) family that is an important drug target for asthma and COPD. Clinical studies coupled with biochemical data have identified a critical receptor variant, Thr164Ile, to have a reduced response to agonist-based therapy, although the molecular mechanism underlying this seemingly ``non-deleterious'' substitution is not clear. Here, we couple molecular dynamics simulations with network analysis and free-energy calculations to identify the molecular determinants underlying the differential drug response. We are able to identify hydration sites in the transmembrane domain that are essential to maintain the integrity of the binding site but are absent in the variant. The loss of these hydration sites in the variant correlates with perturbations in the intra-protein interaction network and rearrangements in the orthosteric ligand binding site. In conjunction, we observe an altered binding and reduced free energy of a series of agonists, in line with experimental trends. Our work identifies a functional allosteric pathway connected by specific hydration sites in beta(2)AR that has not been reported before and provides insight into water-mediated networks in GPCRs in general. Overall, the work is one of the first step towards developing variant-specific potent and selective agonists.
Keywords: beta(2)-Adrenergic receptor; G protein coupled receptor; GPCR; molecular dynamics; Pharmacogenetics; SNP

Molecular characterization of the beta(2)-like octopamine receptor of helicoverpa armigera - Gujar, Nidhi; Nikte, V, Siddhanta; Joshi, Rakesh S.; Joshi, Manali (Journal of Membrane Biology, 2021)
Helicoverpa armigera is a devastating polyphagous and cosmopolitan crop pest. There are reports of this insect being resistant to a variety of pesticides raising concern worldwide. The Octopamine (OA) binding beta(2)-like receptor (OAR), a GPCR, is widely distributed in the nervous system of the insect and plays essential roles in the physiology and development and thus is an important target for insecticides. Yet, the molecular characterization of the H. armigera OAR (HarmOAR) and rational design of compounds based on this receptor is lacking. As a first step, we performed multiple sequence alignment of all insect OARs, which revealed that the sequences contained all conserved class A GPCR motifs. Phylogenetic studies showed clade-specific variations in the protein sequences primarily arising owing to differences in the ICL3 loop region. Further, a structural model of HarmOAR was built using the inactive human beta(2)AR as a template. 0.9 mu s atomistic simulations revealed conserved inter helical contacts and water molecules of HarmOAR. The detailed binding of octopamine was studied using molecular docking and 0.3 mu s atomistic simulations. Twenty-two insecticides active against octopamine receptors of other insects were compiled and docked to HarmOAR followed by rescoring with binding free energies to prioritize them for H. armigera. Our study suggests alpha-terpineol to be a good candidate as an insecticide or insect repellent for Helicoverpa armigera.
Keywords: docking; Helicoverpa armigera; Insecticides; molecular dynamics; Octopamine receptor; Phylogeny

Water mediated allosteric network in beta 2AR T164I variant modulates agonist binding affinity - Nikte, Siddhanta V.; Sonar, Krushna; Tandale, Aditi; Sengupta, Durba; Joshi, Manali (European Biophysics Journal with Biophysics Letters, 2021)

Molecular determinants of GPCR pharmacogenetics: deconstructing the population variants in β2-adrenergic receptor - Joshi, Manali; Nikte, Siddhanta; Sengupta, Durba (Advances in Protein Chemistry and Structural Biology, 2022)
G protein-coupled receptors (GPCRs) are membrane proteins that play a central role in cell signaling and constitute one of the largest classes of drug targets. The molecular mechanisms underlying GPCR function have been characterized by several experimental and computational methods and provide an understanding of their role in physiology and disease. Population variants arising from nsSNPs affect the native function of GPCRs and have been implicated in differential drug response. In this chapter, we provide an overview on GPCR structure and activation, with a special focus on the β2-adrenergic receptor (β2-AR). First, we discuss the current understanding of the structural and dynamic features of the wildtype receptor. Subsequently, the population variants identified in this receptor from clinical and large-scale genomic studies are described. We show how computational approaches such as bioinformatics tools and molecular dynamics simulations can be used to characterize the variant receptors in comparison to the wildtype receptor. In particular, we discuss three examples of clinically important variants and discuss how the structure and function of these variants differ from the wildtype receptor at a molecular level. Overall, the chapter provides an overview of structure and function of GPCR variants and is a step towards the study of inter-individual differences and personalized medicine.

State-dependent dynamics of extramembrane domains in the β2-adrenergic receptor - Nikte, Siddhanta V.; Joshi, Manali; Sengupta, Durba (Proteins- Structure Function and Bioinformatics, 2024)
G protein-coupled receptors (GPCRs) are membrane-bound signaling proteins that play an essential role in cellular signaling processes. Due to their intrinsic function of transmitting internal signals in response to external cues, these receptors are adapted to be highly dynamic in nature. The beta(2)-adrenergic receptor (beta 2AR) is a representative member of the family that has been extensively analyzed in terms of its structure and activation. Although the structure of the transmembrane domain has been characterized in the different functional states of the receptor, the conformational dynamics of the extramembrane domains, especially the intrinsically disordered regions are still emerging. In this study, we analyze the state-dependent dynamics of extramembrane domains of beta(2)AR using atomistic molecular dynamics simulations. We introduce a parameter, the residue excess dynamics that allows us to better quantify receptor dynamics. Using this measure, we show that the dynamics of the extramembrane domains are sensitive to the receptor state. Interestingly, the ligand-bound intermediate R' state shows the maximal dynamics compared to either the active R*G or inactive R states. Ligand binding appears to be correlated with high residue excess dynamics that are dampened upon G protein coupling. The intracellular loop-3 (ICL3) domain has a tendency to flip towards the membrane upon ligand binding, which could contribute to receptor ``priming.'' We highlight an important ICL1-helix-8 interplay that is broken in the ligand-bound state but is retained in the active state. Overall, our study highlights the importance of characterizing the functional dynamics of the GPCR loop domains.
Keywords: allosteric pathway; beta-2 adrenergic receptor; extramembrane domains; GPCR; loop dynamics; protein dynamics; protein network

Is GCR1 the GPR157 of plants? - Gotkhindikar, Aditi; Chakravorty, David; Sengupta, Durba; Joshi, Manali; Assmann, Sarah M. (PLANT PHYSIOLOGY, 2025)